Using Formative Video Competencies and Summative In-Person Competencies to Examine Preparedness for Entry-Level Professional Practice - Hoepner, Jerry K.; Hemmerich, Abby L. (Seminars in Speech and Language, 2020)
A key element of competency-based education is assessment. Effective assessment requires access to a core set of expectations that match a learner's level of preparation. Miller's triangle provides a framework for establishing appropriate expectations that move learners from novice to entry-level clinicians. Formative assessment and feedback are a crucial part of facilitating learning in this context. A pilot investigation was conducted to examine the effects of a formative, video competency on performance in a summative, live competency. Rubrics were used to score performance on two competencies, an oral mechanism exam (OME) and a clinical bedside swallowing examination (CBSE). Performance on the OME was significantly improved in the summative competency, compared with the formative, video competency. Performance on the CBSE did not change from formative to summative competency. Assessment in competency-based education is important as a measure of readiness for entry-level practice. Formative assessment and feedback can improve preparedness and performance on summative competencies. Detailed, criterion-referenced assessment tools are crucial to identifying performance. While the OME rubric used in this investigation appears to meet that standard, it is likely that the CBSE rubric was not specific enough to detect changes.
Keywords: formative assessment; feedback; summative assessment; Miller's pyramid